ANALYSIS OF OCCUPATIONAL SAFETY AND HEALTH (OSH) RISKS AT THE STERILIZER STATION USING THE HIRARC METHOD AT PT KHARISMA ISKANDAR MUDA NAGAN RAYA - Yuliani, Irma; Zakiyuddin, Zakiyuddin; Fadillah, Mardi; Is, Jun Musnadi; Murdani, Ihsan (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Occupational Safety and Health (OSH) is a key priority in both government and private palm oil mills. PT Kharisma Iskandar Muda is a company that applies OSH in every production process. Despite preventive efforts, workplace accident risks still exist. Company data shows that in 2023, there were 5 recorded accidents, while in 2024, there were 3 accidents, 1 moderate and 2 near-miss incidents at the sterilizer station. This study aims to analyze potential hazards by calculating risk values, interpreting the results, and recommending controls to reduce accident risks. The research uses a qualitative method with a case study approach at the sterilizer station. Data collection involved field observations, in-depth interviews, and purposive sampling. Risk analysis was conducted using the HIRARC method. The findings identified 6 work activities with potential hazards: 1 activity posed an acceptable risk, 1 moderate risk, 3 substantial risks, and 1 extreme/unacceptable risk. The conclusion indicates signs of potential accidents related to these activities. Recommended controls include daily monitoring, regular electrical panel inspections, improving worker focus, adding safety signage, enhancing SOPs, and ensuring consistent use of personal protective equipment (PPE).